Property maintenance and management at Dataran Maybank building / Mohd Fakhrul Riduan Abd Rahim ... [et al.] - Abd. Rahim, Mohd. Fakhrul Ridzuan; Abd. Rahim, Muhammad. Aswad; Musa, Mohd. Redzwan; Ahmad, Saiful Azni; Abd. Kadir, Salwani Shuhada; Iberahim, Nur Izwani; Muhalid, Siti Zubaidah (1998)
Building maintenance management is one of the important aspects in any property management. The understanding of building maintenance and its field area is a must for the profesional Building Surveyors. Building maintenance covers not only on the building facilities itself.